Summary of Best Evidence to Address Kinesiophobia Post Percutaneous Coronary Intervention: An Evidence-Based Review - Ding L; Li C; Chen L; Huang PY; Bian FF (Patient Preference and Adherence, 2024)
Li Ding,1,* Cong Li,1,* Lu Chen,1 Pei-Yu Huang,1 Fei-Fei Bian2 1Emergency Ward, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou, Jiangsu, 225300, People’s Republic of China; 2Department of Surgical, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou, Jiangsu, 225300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lu, Chen; Pei-Yu Huang, Emergency Ward, The Affiliated Taizhou People’s Hospital of Nanjing Medical University, No. 366 Taihu Road, Taizhou Pharmaceutical High-Tech District, Taizhou, Jiangsu, 225300, People’s Republic of China, Tel +86 13641589385 ; +86 18705267452, Email chenluchen29@126.com; huangpeiyuh@126.comObjective: The objective of this study is to systematically explore and summarize the best evidence on intervention programs for patients with kinesophobia following percutaneous coronary intervention (PCI) to provide a comprehensive reference for clinical practice interventions.Methods: Evidence on interventions for kinesophobia post-PCI was retrieved from Chinese and international integrated databases, treatment guidelines, and websites of professional associations, including systematic reviews and expert consensuses. The evidence considered in this study extends up to May 2022, encompassing information available since the inception of the databases. Two researchers independently evaluated the articles included in the review and extracted and summarized the available evidence.Results: By extracting and integrating data from the 14 articles included in this review, we identified six categories: pre-intervention assessment, psychological intervention, health education, rehabilitation training, social support, and quality control. A total of 21 pieces of evidence were summarized, including mental health assessment, physical fitness evaluation, timing and content of health education, development of personalized exercise prescriptions, and risk control.Conclusion: In clinical settings, using evidence-based practices requires developing feasible intervention programs based on comprehensive consideration of hospital resources, allocation of medical personnel, and consideration of patients’ preferences to reduce the kinesophobia of patients post-PCI and improve their compliance with exercise rehabilitation.Keywords: evidence-based nursing, evidence summary, intervention, kinesophobia, post-PCI